Tafonomía en la Sierra de Atapuerca, Burgos (España) - Fernández-jalvo, Yolanda (Coloquios de Paleontología, 2003)
Small mammal taphonomic studies have been conducted at several sites of the Sierra de Atapuerca cave complex (Gran Dolina, Penal and Galería). These studies have provided an important information about the site formation and the evolution of the different cavities. Alterations observed on small mammal fossils at the succeeding units of each site have informed on different agents that have brought small mammal remains into the caves. Modifications observed on these fossils have provided evidence of a high incidence of predators that produced the different associations. Indirectly, predators inferred from taphonomic modifications recorded on these small mammal fossils together with the taphonomic processes occurred on these sites have also provided information about palaeo-biological and palaeoenvironmental aspects during the Pleistocene. We have, also, been able to recognize different stages during the site formation. Processes of resedimentation and processes of reelaboration affecting small mammal fossil associations have been recognized. Finally, hypothesis on sedimentary correlation between sites and the karst evolution have been contrasted using taphonomic data. Fossil bone surface modifications have also been studied on humans recovered from Sierra de Atapuerca sites (Gran Dolina TD6-Aurora and Sima de los Huesos). This study has increased our knowledge on human behaviour, apart from the site formation of these two sites. Results from these studies illustrate different aspects that taphonomy may investigate and the interest and repercussion that taphonomic studies may have in other disciplines such as palaeoecology and biostratigraphy
Keywords: Taphonomy; Sierra de Atapuerca; Micromammals; Hominids